Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/hmg/ddt017
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiles in Tc1 mice implicate novel pathway perturbations in the Down syndrome brain

Abstract: Tc1 mouse model of Down syndrome (DS) is functionally trisomic for ∼120 human chromosome 21 (HSA21) classical protein-coding genes. Tc1 mice display features relevant to the DS phenotype, including abnormalities in learning and memory and synaptic plasticity. To determine the molecular basis for the phenotypic features, the levels of 90 phosphorylation-specific and phosphorylation-independent proteins were measured by Reverse Phase Protein Arrays in hippocampus and cortex, and 64 in cerebellum, of Tc1 mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 53 publications
5
46
1
2
Order By: Relevance
“…Slides were stored at 4°C until use. Antibody screening was carried out as previously described (Ahmed et al, 2013). In brief, slides were incubated in blocking solution (3% bovine serum albumin; Sigma-Aldrich Co., St. Louis, MO) in Trisbuffered saline/0.1% Tween 20 (TBST) for 4 hours, followed by overnight incubation at 4°C with primary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slides were stored at 4°C until use. Antibody screening was carried out as previously described (Ahmed et al, 2013). In brief, slides were incubated in blocking solution (3% bovine serum albumin; Sigma-Aldrich Co., St. Louis, MO) in Trisbuffered saline/0.1% Tween 20 (TBST) for 4 hours, followed by overnight incubation at 4°C with primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Antibody signal for each spot was normalized to the corresponding signals from staining a different slide with the general protein stain SyproRuby, following the manufacturer's instructions (Invitrogen). Details of quantitation and review of data quality and reproducibility were as previously described (Ahmed et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Second, the Ts65Dn is also trisomic for a small centromeric segment of mouse chromosome 17 that is not orthologous to HSA21. It has recently been shown that this segment is more gene rich than previously assumed, and indeed includes 50 protein coding genes [56], among them paralogs of some HSA21 genes, including SYNJ2 (see previously for paralog SYNJ1) and TIAM2, plus several Dynein light chain genes whose increased dosage could influence endosomal transport. Thus, the genetic basis for the phenotype of the Ts65Dn is more complex and may not be identical to DS.…”
Section: Ds Animal Models To Understand Admentioning
confidence: 99%
“…Gardiner and collaborators have shown that Tc1 mice show many of the phenotypes characteristic of DS, including abnormalities in learning and memory and synaptic plasticity [36]. In comparison to Ts65Dn mice, the Tc1 exhibit elevated S100B calcium-binding protein, AMPK, and the mTORC1 proteins RAPTOR and downstream kinase P70S6 [62], which are important regulators of cellular metabolism and aging. Therefore, these mice may represent a novel and yet fairly unexplored model for DS, aging and AD.…”
Section: Summary Of Mouse Models Of Down Syndromementioning
confidence: 99%